Directive Speech Acts on Teaching Styles of Online Learning Mentor in Ruangguru Application - Putri, Ervin Oktaviani Herdianti; Haryadi, Haryadi; Wahyudi Joko, Bernadus (Universitas Negeri Semarang, 2023)
Speech acts in learning interactions are one of the interesting language studies to be studied because this is not only related to linguistic aspects but also affects social culture. This research is motivated by the mentor's speech acts in delivering learning materials with their own style or characteristics. Based on these problems, directive speech acts are needed in the mentor's teaching style to attract students' attention in learning activities. So how does the mentor's directive speech act function in the Ruangguru application online teaching style. The purpose of this study is to analyze the directive speech acts that contain directive functions in the mentor's (Master Teacher) speech in Ruangguru online learning application. This research uses a qualitative descriptive approach. The data were collected using the listening method, followed by the involved the conversation observation technique, record, and note. The results of the study showed that the mentor's (Master Teacher) speech in Ruangguru online learning application found several speeches that contain pragmatic functions of inviting, ordering, requesting, forcing, challenging, urging, and suggesting.